2014
DOI: 10.1002/ldr.2308
|View full text |Cite
|
Sign up to set email alerts
|

Soil Conservation Through Sediment Trapping: A Review

Abstract: Preventing the off‐site effects of soil erosion is an essential part of good catchment management. Most efforts are in the form of on‐site soil and water conservation measures. However, sediment trapping can be an alternative (additional) measure to prevent the negative off‐site effects of soil erosion. Therefore, not all efforts should focus solely on on‐site soil conservation but also on the safe routing of sediment‐laden flows and on creating sites and conditions where sediment can be trapped. Sediment trap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
180
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(188 citation statements)
references
References 90 publications
(145 reference statements)
5
180
0
3
Order By: Relevance
“…1) (Bisantino et al, 2015;Keesstra et al, 2016;Novara et al, 2016;Prosdocimi et al, 2016c). However, to reduce the high soil erosion rates, more conservation-minded soil management practices have also been used such as mulching (Cerdà et al, 2015;Costantini et al, 2015;Jordán et al, 2011;Prosdocimi et al, 2016bProsdocimi et al, , 2016c, cover crops (Novara et al, 2011), rock fragments (Blavet et al, 2009), natural grassing (Grimaldi et al, 2015;Mekonnen et al, 2015a;Mekuria et al, 2016;Raclot et al, 2009) and geotextiles (Giménez Morera et al, 2010;Mekonnen et al, 2015b;Mengistu et al, 2016). Furthermore, new approaches to evaluate incentives for the adoption of agri-environment measures in degraded and eroded vineyards have been implemented (Galati et al, 2015) and mulching is one of those successful strategies (Prosdocimi et al, 2016c).…”
Section: Introductionmentioning
confidence: 99%
“…1) (Bisantino et al, 2015;Keesstra et al, 2016;Novara et al, 2016;Prosdocimi et al, 2016c). However, to reduce the high soil erosion rates, more conservation-minded soil management practices have also been used such as mulching (Cerdà et al, 2015;Costantini et al, 2015;Jordán et al, 2011;Prosdocimi et al, 2016bProsdocimi et al, , 2016c, cover crops (Novara et al, 2011), rock fragments (Blavet et al, 2009), natural grassing (Grimaldi et al, 2015;Mekonnen et al, 2015a;Mekuria et al, 2016;Raclot et al, 2009) and geotextiles (Giménez Morera et al, 2010;Mekonnen et al, 2015b;Mengistu et al, 2016). Furthermore, new approaches to evaluate incentives for the adoption of agri-environment measures in degraded and eroded vineyards have been implemented (Galati et al, 2015) and mulching is one of those successful strategies (Prosdocimi et al, 2016c).…”
Section: Introductionmentioning
confidence: 99%
“…On-site sediment trapping measures can trap sediment and thus limit sediment export from agricultural fields Lambrechts et al, 2014;Mekonnen et al, 2014b). Grass barriers are among the many on-site measures that play a significant role in trapping sediments from overland flow (Ritsema, 2003;Blanco-Canqui et al, 2004;McKergow et al, 2004;Stroosnijder, 2009;Wanyama et al, 2012).…”
Section: Importance Of Soil Loss Reduction By Grass Barriersmentioning
confidence: 99%
“…Sediment trapping was found to be effective when structural and vegetative measures combined together (Mekonnen et al, 2014b). Erktan et al (2013) investigated the role of morphological diversity of plant barriers in sediment trapping and found that grass barriers performed best in trapping sediment however, the morphological diversity was significantly impaired by STE.…”
Section: Importance Of Soil Loss Reduction By Grass Barriersmentioning
confidence: 99%
See 2 more Smart Citations